The Geriatric Nutritional Risk Index as a Prognostic Factor in Patients with Advanced Non-Small-Cell Lung Cancer. (31st December 2021) - Peng, Si-Min; Yu, Na; Ren, Jin-Jin; Xu, Jia-Ying; Chen, Guo-Chong; Yang, Jin-Rong; Li, Zeng-Ning; Du, Hong-Zhen; Li, Da-Peng; Zhang, Yu-Song; Qin, Li-Qiang
Abstract: The Geriatric Nutritional Risk Index (GNRI) is widely applied as a prognostic factor in different cancers. We aimed to analyze the prognostic value of the GNRI in 257 patients diagnosed with advanced non-small-cell lung cancer (NSCLC). Patients with GNRI >98, 92–98, and <92 were grouped into normal, low risk and moderate/high risk groups, respectively. There were 45.1% patients at risk for malnutrition. Kaplan-Meier survival curves indicated that patients with lower GNRI scores had a poorer overall survival (OS). Two-year OS for normal, low risk and moderate/high risk groups were 57.4%, 42.3% and 15.8%, respectively. In multivariate survival analysis, GNRI (<92), body mass index (BMI, ≥24 kg/m2), combined therapy, hemoglobin and neutrophil-to-lymphocyte ratio (NLR) were independent prognostic factors of OS. Stratifying by age groups, GNRI (<92), hemoglobin and NLR were independent prognostic factors of OS in patients aged <65 years. GNRI (<92), smoking, BMI (≥24 kg/m2) and platelet-to-lymphocyte ratio were independent prognostic factors of OS in patients aged ≥65 years. In conclusion, GNRI was a significant prognostic factor in advanced NSCLC patients regardless of age. A decreased GNRI may be considered as a clinical trigger for nutritional support in advanced NSCLC patients, though additional studies are still required to confirm the best cut-point.